ANALISIS PENGAWASAN IZIN TINGGAL WARGA NEGARA ASING DALAM WILAYAH KANTOR IMIGRASI KELAS II TPI LHOKSEUMAWE - Ricky Muliawan Hansyar; Asrul Fahmi (Jurnal Ilmu Sosial dan Ilmu Politik Malikussaleh (JSPM), 2024)
Research is about "Oversight of residence permits of Foreign Citizens" at the Class II Immigration Office of TPI Lhokseumawe. This research aims to describe the supervision of a Foreign Citizens' residence permit in violation of the applicable residence permit provisions and to find out the obstacles in the supervision of a Foreign Citizens' residence permit in the area of the Class II Immigration Office of TPI Lhokseumawe. This research uses a qualitative approach, which aims to describe and analyze the supervision of foreigners' residence permits. The techniques of data collection are observation, interviews, and documentation, and then the data analysis techniques through the steps of data collection, data reduction, data presentation, and conclusions The results of conclude that the supervision of the residence permit of Foreign Citizens within the area of the Class II Immigration Office of TPI Lhokseumawe has been carried out administrative and field supervision accurately, timely, thoroughly objectively, and fully coordinated. Besides, obstacles in the supervision of residency permits of Foreign Citizens consisted of lack of supervision apparatus resources, lack of community coordination, and the wide scope of supervision. An evaluation is needed so that supervision of residency permits within the area of the Class II Immigration Office of TPI Lhokseumawe runs by following the set targets for surveillance operations.